A critical discourse analysis of Malaysian corporate social responsibility reports / Kumaran a/l Rajandran - Rajandran, Kumaran (2015)
This research studies the communication of corporate social responsibility (CSR) in Malaysian CSR reports. CSR is a new domain in Malaysia and CSR reports are a relatively new register for Malaysian corporations. There is little research for CSR reports, compared to other registers in corporate discourse. Two major strands of investigation identified are for adherence and communication. CSR adherence studies conformity to various standards but not language and image and CSR communication has studied language more than image but it often does not study recontextualization and ideology. This research can contribute to research on CSR communication by conducting a detailed analysis of Malaysian CSR reports. It is grounded in Fairclough’s 3-dimensional critical discourse analysis (CDA) model, which consists of 3 dimensions of text, discourse practice and social practice. The model is employed on a corpus of 27 CSR reports from 2009 to 2011 from 10 major foreign and local corporations incorporated in Malaysia. The two sections analyzed in these reports are the CEO Statement and Environment Section. The analysis adopts a micro to macro approach, from text to discourse practice to social practice. Text is analyzed by automated corpus processes and manual Systemic-Functional Multimodal Discourse Analysis (SF-MDA). Corpus processes covers frequency and concordance while SF-MDA covers FIGURATION and APPRAISAL for language and Representation and Interaction for image. The automated and manual analyses show that CEO Statements and Environment Sections employ selected language and image features to present CSR. CEO Statements have three major entities of corporations, stakeholders and CSR performance while Environment Sections have three major entities of corporations, environmental risks or resources and environmental initiatives. Both sections portray their entities through expounding with positive valuation. Then, discourse practice is analyzed by focusing on intertextuality and interdiscursivity. CSR reports employ conventionalized and standardized texts and discourses. The texts cited are organized along an intertextual cline, where a corporation’s right to determine or influence the content of texts diminishes as the cline extends rightwards. Citing right-leaning texts improves the credibility of CSR reports. The discourses incorporated are public knowledge but may be easily reproduced and are present in other domains. Incorporating these discourses improves the accessibility of CSR reports. Next, social practice is analyzed through social theories. The corporate context of Malaysia has 4 major parties, namely the Malaysian Government, Bursa Malaysia, corporations and stakeholders. The Malaysian Government and Bursa Malaysia establish directives to engage in and disclose CSR. Corporations invest economic capital in CSR reports and corporations gain cultural, social and symbolic capitals from CSR reports. Corporations also consider selected stakeholders in CSR reports. This research demonstrates CSR reports as ideological and their ideology represents orthodoxy or the official way to conceptualize the role of corporations, stakeholders and CSR performance for Malaysian corporations. In Malaysia’s capitalist, market-driven economy, CSR may provide social legitimacy to maintain economic legitimacy.